2018
DOI: 10.15296/ijwhr.2020.34
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Behaviors in Physiological Birth Versus Cesarean Section

Abstract: Objectives: Attachment can be described as a powerful bond between two individuals, in this case, between the mother and child. This process is started during pregnancy and completed after childbearing. Thus, delivery time, as a turning point between two stages of attachment is very important. Accordingly, the present study aimed to investigate the probable relations between the mother to child attachment and the mode of delivery. Materials and Methods: In this descriptive-analytical study, 260 pregnant women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…The results of the current study indicated that level of attachment seem to differ by the types of child delivery. Normally born children had higher levels of attachment than cesarean children, which was consistent with the previous research findings (Ebrahimi et al, 2020;Zanardo et al, 2016;Zavardehi, Faramarzi and Mirzaeian, 2018). Zavardehi, Faramarzi and Mirzaeian, (2018).…”
Section: Result Discussion and Suggestionssupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the current study indicated that level of attachment seem to differ by the types of child delivery. Normally born children had higher levels of attachment than cesarean children, which was consistent with the previous research findings (Ebrahimi et al, 2020;Zanardo et al, 2016;Zavardehi, Faramarzi and Mirzaeian, 2018). Zavardehi, Faramarzi and Mirzaeian, (2018).…”
Section: Result Discussion and Suggestionssupporting
confidence: 91%
“…Zavardehi, Faramarzi and Mirzaeian, (2018). Iranian children born in cesarean section were found to have less attachment compared to normally born children, which was further supported by Ebrahimi et al,(2020). Similar findings were also obtained in Western studies.…”
Section: Result Discussion and Suggestionssupporting
confidence: 81%
See 1 more Smart Citation
“…22 Literature reports different results concerning maternal attachment when comparing cesarean section and vaginal delivery. 23 Although there is some evidence showing that nonvaginal or traumatic delivery makes it difficult to establish a bond between mother and baby, [24][25][26][27] in our study, it was determined that women who gave birth with anomaly by cesarean section developed more attachment to babies than women who gave birth normally. This result makes the study different from other studies.…”
Section: Discussionmentioning
confidence: 56%
“…Over recent years, the rate of cesarean sections has increased, and one of the reasons for this rise stems from the anxiety associated with vaginal birth 22 . Literature reports different results concerning maternal attachment when comparing cesarean section and vaginal delivery 23 . Although there is some evidence showing that nonvaginal or traumatic delivery makes it difficult to establish a bond between mother and baby, 24–27 in our study, it was determined that women who gave birth with anomaly by cesarean section developed more attachment to babies than women who gave birth normally.…”
Section: Discussionmentioning
confidence: 99%